-1=k-9

Simple and best practice solution for -1=k-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1=k-9 equation:


Simplifying
-1 = k + -9

Reorder the terms:
-1 = -9 + k

Solving
-1 = -9 + k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
-1 + -1k = -9 + k + -1k

Combine like terms: k + -1k = 0
-1 + -1k = -9 + 0
-1 + -1k = -9

Add '1' to each side of the equation.
-1 + 1 + -1k = -9 + 1

Combine like terms: -1 + 1 = 0
0 + -1k = -9 + 1
-1k = -9 + 1

Combine like terms: -9 + 1 = -8
-1k = -8

Divide each side by '-1'.
k = 8

Simplifying
k = 8

See similar equations:

| x-3/10=4x | | -3c+7=-17 | | 7n+x=3x-n | | 6n+3=-4n+7 | | x²√25/289 | | 12x-3y=-36 | | (6x-4)(4n-5)= | | -78=3j+7-8j | | 25=40+s | | 27x=28 | | 4x^2+14-210=0 | | p-3/8 | | 3x/y=6 | | X+17=151 | | (12-5i)(7i+5)= | | A+2(y+3)=y+7 | | 6f-4+2f=20 | | 6x-8+15=-9 | | -6x-3x=5(x-5)-3(7x+1) | | 3(-0.8+0.4y)+2y=0 | | (7r-4)(r+5)-(2r-1)(r+5)= | | 2(3y+7)=44 | | (3x+1)+(8x-24)= | | 0=.333x+4 | | -y^2=0 | | 14u-9u=45 | | 13=y+20 | | 3(-5+5x)-2x=11 | | t^2-2t=(t+3) | | 5+4w=-3 | | -3(w+4)=3w-30 | | 8+3x=19+x |

Equations solver categories